Capital withdrawal from Kazakhstan: Challenges and prospects of the recovery mechanism for stolen assets - Albekova, M.G.; Gilmour, P. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The purpose of this research article is to study the problem of capital withdrawal from Kazakhstan and the importance of returning stolen assets in protecting the property rights of citizens, organizations and the state. The article examines the multi-step process of returning criminal money, highlighting the complexities and difficulties such as identifying assets, identifying their beneficiaries and returning them to the country of origin. The article reviews the legal framework of international and national legislation on the return of stolen assets, as well as the positive experience of Kazakhstan and other countries in this direction. The focus is on the new law of the Republic of Kazakhstan of July 12, 2023, which focuses on the return of illegally acquired assets to the state. In addition, the article provides an overview of the challenges and prospects in addressing this pressing problem and emphasizes the need for effective measures to restore social justice in society. This paper discusses in detail the challenges countries face in recovering stolen assets in the context of existing differences in legal systems, increasing financial flows, and offshore zones.
Қазақстаннан капиталды шығару: ұрланған активтерді қайтару тетігінің сын-қатерлері мен перспективалары
Вывод капитала из Казахстана: вызовы и перспективы механизма возврата похищенных активов
Keywords: asset recovery; illicit proceeds; stolen funds; beneficiaries; offshore; international co-operation